Meningkatkan Hasil Belajar Materi Kemampuan dan Keterbatasanku Melalui Problem Based Learning Peserta Didik pada Kelas 7 SMP Negeri 12 Kota Surakarta - Maria Andriati Tri Utami (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study explores the impact of Problem-Based Learning (PBL) on improving students' learning outcomes in the subject "Kemampuan dan Keterbatasanku" (My Abilities and Limitations) at SMP Negeri 12 Surakarta. Using Classroom Action Research (CAR), the study was conducted in two cycles involving Grade 7 students. Data were collected through tests, interviews, and observations, showing improvements in both cognitive understanding and student engagement. Problem Based Learning proved effective in helping students connect learning to real-life problems, fostering critical thinking and collaboration. Despite initial challenges in participation and motivation, students' outcomes significantly improved by the second cycle, with 75% of students meeting the learning goals. The findings suggest that Problem Based Learning can be an effective teaching model to enhance students' understanding and promote independentl earning.